Differentiated approach in the treatment of fractures of the distal humerus in children based on the use of bioabsorbable implants - M. Lyutkevych (Хірургія дитячого віку, 2022)
In the practice of pediatric traumatologists there are a number of complex problems in the treatment of fractures of the distal humerus, which require a differentiated approach: atraumatic anatomical reposition with minimal damage to active growth zones, minimal damage to articular cartilage during surgery, stable fixation and early rehabilitation.